Antioxidant In Reducing MDA Conditions and Increasing SOD Conditions in White Rats (Rattus norvegicus) Wistar Strain Given a High Cholesterol Diet and Induced More Physical Activity - Riana, Nova; Putri, Lenni Dianna; Novriani, Erida (Newinera Publisher, 2024)
Sedentary lifestyles increase the risk of morbidity and infectious illnesses. Physical exercise can improve immune function but can lead to increased oxidants and reactive oxygen species (ROS), damaging cells and tissues. Crucial in mitigating the cellular damage caused by free radicals are antioxidants, including non-enzymatic antioxidants such as glutathione, vitamins C and E, and others. Moderate to high-intensity physical exercise can result in an increase in ROS and a reduction in SOD. Grape seeds are rich in antioxidants, which have been shown to neutralize free radicals and protect against inflammation, bacteria, ulcers, and cancer. These antioxidants, including phenols and proanthocyanidins, are beneficial to health and have applications in various industries, including energy production, cosmetics, and pharmaceuticals. Research is also being conducted to explore their antioxidant effects on MDA levels. Grape seed extract was tested for its impact on malondialdehyde (MDA) levels in the blood of male Wistar strain white rats. Rats' MDA levels decreased following four weeks of treatment. Rat cages, digital scales, an MDA test kit, and SPSS were some of the equipment used in the study. Grape seed extract effectively reduces MDA levels in rats with hypercholesterolemia, resulting in weight loss and a lee index below 0.3, and increases SOD levels, indicating potential for human use.